Perlindungan Hukum Kekayaan Intelektual Terhadap Pengrajin Kerajinan Tangan - Ida Nadirah (DE LEGA LATA: JURNAL ILMU HUKUM, 2020)
The arrangement of intellectual property rights of handicraft craftsmen in Indonesia is the result of transplants from the TRIP’s Agreement and the Paris Convention for the Protection of Industrial Property (Paris Convention) which has a capitalist paradigm. This regulation is difficult to implement optimally, because the background values and cultures are different. However, due to juridical and psychological consequences, Indonesia has agreed on the GATT (General Agreement of Tariff and Trade) and also agreed on the GATT / WTO (World Trade Organization) framework, finally Indonesia ratified through Law No. 7 of 1994.The great expectation of the Intellectual Property Rights Law can be implemented, but the fact is that Law No. 31 of 2000 is still not optimally applied mainly by handicraft craftsmen. This is proven by the fact that the number of applicants is getting worse because of the degradation of creativity and not fulfilling the values of social justice. An alternative step in bridging is to internalize the Pancasila values into the Intellectual Property Rights Act as "spirit or soul" which is expected to be able to provide justice for the community of handicraft craftsmen, so that it can spur the development of the creativity of the next handicraft craftsmen.